Effect of weight and storage period of hatching eggs on hatching parameters of the Japanese Quail (Coturnix japonica) - بشرى العيسى; جعفر أحمد (Latakia University Journal -Biological Sciences Series, 2022)
To find out the optimum incubation egg weight and storage period, which gives the best results for hatching and the vitality of the resulting chicks, a study was conducted using 360 eggs obtained from a specialized Japanese Quail farm, where the eggs were divided into two groups: the first includes 180 eggs dedicated to weight treatments, which are three categories: small eggs T1ws (less than 10 g),T2wm medium eggs (12-10 g), T3wb large eggs (greater than 12 g). The second group is dedicated to storage period treatments and includes 180 eggs divided into three categories: Td3 stored for 3 days, Td7 stored for 7 days, Td10 stored for 10 days. The eggs were incubated in the hatchery for the poultry laboratory for a period of 17 days.This study concluded that there was a strong significant correlation (P<0.05) between the weight of eggs and the weight of the hatched chicks, and its value was 0.96, and there was a significant effect of egg weight on the standards of hatching and incubation period, where the treatment T1ws recorded a significant decrease in the percentage of hatching, fertilization and survival rate, and recorded a significant increase in the percentage of total fetal mortality, and the treatment T2wm gave the best results of hatching standards. The incubation time was recorded for T1ws (386.5h) young eggs.The duration of storage significantly affected hatching parameters and incubation period, while it did not have a significant effect on the fertilization rate. Storing eggs for a period not exceeding 3 days achieves a high hatching rate and chicks with good vitality and weight.